Pemanfaatan Internet untuk Meningkatkan Minat Baca Mahasiswa PLS IKIP Siliwangi - Shindriani Putri (IKIP Siliwangi, 2020)
Abstract This research is motivated by the use of the internet by university student and their lack of interest in university student coming to the library, as well as their lack of interest in reading. The lack of interest in reading university student depends on the role of parents in paying attention to unoversity student activities. Low interest in reading can affect the progress of the nation's generation. The theory used in this research is technology theory, literacy theory. The method used is qualitative with interview and questionnaire techniques. The results of this study, namely the development of technology in students' low interest in reading. University student interest in reading in reading can be seen from the participation of students when attending lectures and the lack of interest in reading university students is caused by the lack of attention, support, the rapid technological factors, library management and supervision of the family of its activities.Abstrak Penelitian ini dilatar belakangi oleh penggunaan internet oleh mahasiswa dan kurang minatnyamahasiswa untuk datang ke perpustakaan, serta kurang minatnyamahasiswa untuk membaca. Kurangnya minat membaca mahasiswa tergantung pada peran orang tua dalam memperhatikan kegiatan mahasiswa. Minat yang rendah dalam membaca dapat mempengaruhi kemajuan generasi bangsa. Teori yang digunakan dalam penelitian ini adalah teori teknologi, teori literasi. Metode yang digunakan adalah kualitatif dengan teknik wawancara dan kuesioner. Hasil penelitian ini, yaitu dengan adanya perkembangan teknologi minat baca mahasiswa rendah. Minat baca mahasiswa dalam membaca dapat dilihat dari keikutsertaan mahasiswa ketika menghadiri kuliah dan rendahnya minat membaca mahasiswa disebabkan oleh kurangnya perhatian, dukungan, faktor pesatnya teknologi, pengelolaan perpustakaan dan pengawasan dari keluarga terhadap kegiatannya.